2009
DOI: 10.1007/s00024-009-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Curie-point Depth from Spectral Analysis of Magnetic Data in Erciyes Stratovolcano (Central TURKEY)

Abstract: Curie-point depth and heat flow values of the Erciyes region are determined to identify the thermal regime of the Central Anatolia by applying the spectral analysis method to the magnetic anomaly data. To compute the spectrum of the data, the magnetic anomaly of the region is transformed into 2-D Fourier domain to attain the average Curie depth. This method is useful in determining the top boundary of magnetic anomaly sources and reveals the Curie depth as 13.7 km in the study area. The obtained results imply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…Studies on the Curie temperature depth have been performed by some researchers (ATES¸et al, 2005;AYDIN et al, 2005;DOLMAZ et al, 2005;MADEN et al, 2009b;MADEN 2009;MADEN 2010) in the eastern, western, central and northern Turkey. AYDIN et al (2005) presented the Curie-point isotherm map of Turkey by using the spectral analysis technique applied to aeromagnetic data.…”
Section: Curie Temperature Depth and Heat Flow Density Valuesmentioning
confidence: 99%
“…Studies on the Curie temperature depth have been performed by some researchers (ATES¸et al, 2005;AYDIN et al, 2005;DOLMAZ et al, 2005;MADEN et al, 2009b;MADEN 2009;MADEN 2010) in the eastern, western, central and northern Turkey. AYDIN et al (2005) presented the Curie-point isotherm map of Turkey by using the spectral analysis technique applied to aeromagnetic data.…”
Section: Curie Temperature Depth and Heat Flow Density Valuesmentioning
confidence: 99%
“…For this purpose, the bottom depth of a magnetic source from aeromagnetic data is considered to be the Curie point depth. The CPD estimation from magnetic data has been widely used to determine the thermal structure of the crust in various tectonic settings (Smith et al 1977;Connard et al 1983;Okubo et al 1985;Blakely 1988;Tanaka et al 1999;Dolmaz et al 2005;Ross et al 2006;Maden 2010;Aboud et al 2011;Rao et al 2011;Bansal et al 2013;Hsieh et al 2014;Obande et al 2014;Starostenko et al 2014;Nwankwo and Shehu 2015;Saibi et al 2015;Khojamli et al 2016;Bilim et al 2016). Amirpourasl et al (2010) produced a CPD map of whole Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers AYDıN et al 2005;DOLMAZ et al 2005;BEKTAS¸et al 2007;MADEN et al 2009b;MADEN 2009MADEN , 2010MADEN , 2013 MADEN et al (2009b) found that the Curie point depths fluctuate between 14.3 km in the south and 27.9 km in the north by using magnetic data of the Eastern Pontides. MADEN (2010) computed two Curie point depths as 11.4 and 13.7 km, reflecting the high geothermal potential of the Cappadocia and Erciyes volcanic region.…”
Section: Introductionmentioning
confidence: 99%
“…MADEN (2010) computed two Curie point depths as 11.4 and 13.7 km, reflecting the high geothermal potential of the Cappadocia and Erciyes volcanic region. MADEN (2013) determined the mean Curie point depth value of 25 km, which is thinner than the Moho depth value in the continental areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation